Instructional design and teachers and learners factors affecting active and meaningful participation in online discussion - Pitagan, Ferdinand B. (Animo Repository, 2024)
As more and more learning institutions include online discussion in their curriculum, it is therefore imperative to understand what constituents an active and meaningful participation in online discussion. In view of this, the study aims to explore the following questions: (1) what is active and meaningful participation in online discussion and (2) what are the instructional design and teachers and students factors that affect active and meaningful participation in online discussion? The study will be based on review of literature and related studies. It aims to provide new knowledge and understanding that could serve as theoretical and conceptual basis in designing instruction for online discussion and consequently for online learning.